Prediction model of voltage–time characteristics for SF6 long gap under VFTO and lightning impulse voltage. Issue 4 (12th January 2018) - Zhang, Lu; Wang, Sen; Sun, Lei; Mao, Chen; Pu, Lu; Zhang, Qiaogen
Abstract : Voltage–time ( V – t ) characteristics of the SF6 long gap under very fast transient overvoltage (VFTO) draw wide attention at the high‐voltage transmission systems. In this research, a generating system of VFTO and lightning impulse (LI) up to 2.5 MV was set up. The V – t characteristics for SF6 gaps with hundreds of millimetres length under negative LI and VFTO were researched. Experimental results indicated the rate of rising of V – t curve for the sphere‐plane gap under VFTO was moderate, and V – t curve under LI was rapid, resulting in the intersection of the two types of V – t curves. However, for the rod‐plane gap, the V – t curve under VFTO was below that under LI at 0.5 MPa. The shape of V – t curve had many relationships with discharge propagation velocity in the SF6 gap, which was determined by the gap distance, field non‐uniformity, gas pressure and applied voltages. Based on analysis of discharge process and physical background of V – t curve, the semi‐empirical formulae were derived and the prediction model was established. It was demonstrated the predicted V – t curves could accurately predict breakdown characteristics of long SF6 gas gaps